WRIDY: MULTISENSORY WRITING APPROACH IN MOBILE APPLICATION FOR KIDS WITH LEARNING DISABILITIES INCLUDING DYSLEXIA - T.N., Wee; Rehman Ullah, Khan; Yin, Bee Oon; Lee, J.C. (iated.org, 2021)
Handwriting development begins as early as infancy when children are first able to grasp a writing object and leave a mark on the paper. Handwriting is linked with brain functioning; experts suggest that handwriting skill lightens a student’s cognitive load. With consistent handwriting practice, it becomes less demanding and more automatic, enabling students critical thinking and thought organization. The lack of writing skill decreases kids’ capacity to carry out higher-order skills. Most of the writing intervention approaches are not multisensory and some are using substances that may be dangerous for kids such as sand or shaving cream or pipe cleaners or play-doh etc. These issues become more challenging for kids with a learning disability such as dyslexia. This empirical gap in the multisensory writing system is the target of this research. A multisensory mobile application (Wridy) is designed and developed to support kids with learning disabilities. Wridy is an early-stage multisensory writing intervention tool. It uses a dyslexia-friendly user interface, fonts and colour. Wridy is demonstrated to the teachers of the Dyslexia Association Kuching, Malaysia. The results of the survey show that Wridy is helpful and useful in learning writing alphabets especially for kids with learning disabilities such as dyslexia.